Correlation of Nutritional Status, HbA1c, and Duration of Diabetes Mellitus with Amputation Incidence in Patients with Diabetic Foot Ulcers - Hapsari, Putie; Kharisma, Surti Wulan; Yarman, Indra Prasetya; Faried, Ahmad; Djajakusumah, Teguh Marfen; Maryani, Euis (Faculty of Medicine, Universitas Padjadjaran, 2025)
Diabetic foot ulcer (DFU) is a severe complication of diabetes that significantly impairs quality of life and may often lead to amputation, particularly when infections become extensive. This study investigated the correlation of nutritional status, HbA1c levels, and duration of diabetes exposure with the incidence of amputation in DFU patients. Using an observational analytic study with a retrospective cohort design, data from 47 DFU patients treated at the Vascular and Endovascular Surgery clinic and Emergency Room of a hospital from 2019-2024 were analyzed. The majority of subjects were men aged 40-60 years (59.57%). Among the amputee group, 55.31% experienced neuropathy, primarily classified as Wagner's degree 4. Patients requiring amputation had significantly higher levels of urea, creatinine, and leukocytes compared to those who did not. A significant correlation was observed between the incidence of amputation and nutritional status—specifically, serum albumin (r=-0.616) and Body Mass Index (BMI) (r=0.823)—as well as HbA1c levels (r=0.806) and duration of diabetes exposure (r=0.445) (p<0.05). However, the Subjective Global Assessment (SGA) did not show a significant relationship with amputation incidence. The findings of this study suggest that nutritional status, HbA1c levels, and duration of diabetes exposure are significantly correlated with the likelihood of amputation in patients with diabetic foot ulcers (DFU).